2014
DOI: 10.1163/1568539x-00003184
|View full text |Cite
|
Sign up to set email alerts
|

Defensive responses of gopher tortoises (Gopherus polyphemus) are influenced by risk assessment and level of habituation to humans

Abstract: Species that are either sessile or too slow to resort to flight may instead rely on defences such as natural armour or protective structures, but they will still face the same economic decisions as do more mobile species about when to re-emerge from cover. The gopher tortoise (Gopherus polyphemus) is a species of conservation significance due to its important role as an ecosystem engineer and habitat loss due to human activities. In this study, we examined escape responses of gopher tortoises approached by a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…hunting, capture, and handling), or presence of predator‐like animals (e.g. dogs), will also influence animal risk assessment (Gabrielsen & Smith, ; Martinetto & Cugnasse, ; González et al , ; Bates et al , ; Bateman et al , ). Some research has also shown that animals may be more reactive to the visual presence of humans than to anthropogenic noise (Gabrielsen & Smith, ).…”
Section: Level 2: Physiological and Behavioural Responses To Human Prmentioning
confidence: 99%
See 2 more Smart Citations
“…hunting, capture, and handling), or presence of predator‐like animals (e.g. dogs), will also influence animal risk assessment (Gabrielsen & Smith, ; Martinetto & Cugnasse, ; González et al , ; Bates et al , ; Bateman et al , ). Some research has also shown that animals may be more reactive to the visual presence of humans than to anthropogenic noise (Gabrielsen & Smith, ).…”
Section: Level 2: Physiological and Behavioural Responses To Human Prmentioning
confidence: 99%
“…Prior interactions with human activities or natural predation might increase stress responses in further encounters (i.e. sensitization of individuals exposed to hunting, noxious anthropogenic stimuli or high natural predation pressure) (Bejder et al , ; Bateman et al , ). However, human‐induced stress response can be low when animals are naïve to predation risk due to the lack of natural predators or when individuals have been habituated to harmless anthropogenic stimuli (Ydenberg & Dill, ; Helfman, ; Bejder et al , ).…”
Section: Level 2: Physiological and Behavioural Responses To Human Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Turtles that stopped moving remained in place with their neck extended while the observer was in sight, a behavior also reported for box turtles (Terrapene ornata (Agassiz, 1857); Legler 1960). Thus, we walked at least 10 m away to a location that reduced our visibility to the turtle, and that was not between or on the other side of a turtle and water, to observe its reaction (for similar methods, see Bateman et al 2014). After the female finished nesting or fled, we recorded the response to the observer (i.e., continue nesting vs. flee).…”
Section: Methodsmentioning
confidence: 99%
“…FID has been used extensively to test the economic risk-sensitivity hypothesis (Cooper & Frederick, 2007;Ydenberg & Dill, 1986), which predicts that an organism will flee from an approaching predator when the costs of staying outweigh the costs of fleeing. Various factors can influence perception of predation risk, including previous experience with predators (Bateman, Fleming, Jones, & Rothermel, 2014;Cooper & Frederick, 2007;Stankowich, 2009). Based on the observations that threat-conditioned rats freeze for a longer duration compared to controls when presented with a conditioned stimulus, we predicted that, when slowly approached by a novel predator, birds previously chased by the predator would flee sooner (i.e.…”
Section: Threat Conditioningmentioning
confidence: 99%